O papel regulatório do Estado na moderação de conteúdo exercida pelas plataformas de redes sociais - Couto, Natalia de Macedo (2022)
In a digital society, social media platforms increasingly play a central role in the economy and democracy, with power to influence what, how and when information is accessed by an user. To keep the digital environment attractive for the performance of their business model, social media platforms need a healthy space, free from harmful speech (hate speech, disinformation, etc.) and personalized. For this, they moderate the content posted by users and manage the information flow through their recommender systems. This activity calls attention to a procedure without transparency and justification, with decisions that affect the fundamental rights of individuals, such as, for example, those referring to freedom of expression, privacy and data protection and due process. Social networks, today, regulate the private digital space alone, according to their terms of use and the architecture of their algorithmic systems, which, consequently, generates criticism of legitimacy in this governance. Considering that platforms are private entities and in the performance of their activities they can violate fundamental rights, produce externalities and information asymmetry, technical justifications for their regulation by the State are present. However, this regulation, as defended in this work, should not be based on a command and control arrangement, since the presence of the actors that will be affected by the regulation is important for the regulation to be more efficient. The complexity of society and the evolution of institutional arrangements guide the realization of a more responsive regulation, based on the regulation of the procedures addressed in the operation of the activity of social networks and that consider the multiple actors involved. The hypothesis of this work is, therefore, that the State, through the Executive Power, has a role to play in the regulation of social network platforms. Within a co-regulation arrangement, regulatory norms may require participation, transparency and accountability, while taking advantage of the expertise of those regulated. As for the regulatory instrument, this work argues that the most appropriate would be a Regulatory Agency, either through the creation of a new agency or through an existing one.